Contrast-Induced Acute Kidney Injury: Definition, Epidemiology, and Outcome. (10th March 2014) - Meinel, Felix G.; De Cecco, Carlo N.; Schoepf, U. Joseph; Katzberg, Richard
Abstract : Contrast-induced acute kidney injury (CI-AKI) is commonly defined as a decline in kidney function occurring in a narrow time window after administration of iodinated contrast material. The incidence of AKI after contrast material administration greatly depends on the specific definition and cutoff values used. Although self-limiting in most cases, postcontrast AKI carries a risk of more permanent renal insufficiency, dialysis, and death. The risk of AKI from contrast material, in particular when administered intravenously for contrast-enhanced CT, has been exaggerated by older, noncontrolled studies due to background fluctuations in renal function. More recent evidence from controlled studies suggests that the risk is likely nonexistent in patients with normal renal function, but there may be a risk in patients with renal insufficiency. However, even in this patient population, the risk of CI-AKI is probably much smaller than traditionally assumed. Since volume expansion is the only preventive strategy with a convincing evidence base, liberal hydration should be encouraged to further minimize the risk. The benefits of the diagnostic information gained from contrast-enhanced examinations will still need to be balanced with the potential risk of CI-AKI for the individual patient and clinical scenario.